2014
DOI: 10.1039/c4an00250d
|View full text |Cite
|
Sign up to set email alerts
|

Investigating drug induced changes in single, living lymphocytes based on Raman micro-spectroscopy

Abstract: Raman spectroscopy is a powerful tool for label-free, single cell characterization. In many reported studies, a Raman spectrum is acquired from a fraction of the cell volume and used as a representative signature of the whole cell to identify and discriminate between cell populations. It has remained an open question whether this is the most suitable approach since the spectra may not truly represent the cell as a whole and critical biochemical information could therefore be lost. To address this question, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 38 publications
1
60
0
1
Order By: Relevance
“…[67] TheR aman study detected large panitumumab-induced differences in cells expressing wild-type K-Ras,b ut not in cells with oncogenic K-Ras mutations.O ther works monitored the effects of the anticancer drug docetaxel on the morphology and biochemistry of living colon cancer cells, [68] the anticancer drug paclitaxel on MCF-7 breast cancer cells, [69] the chemotherapeutic drug doxorubicin on lymphocytes, [70] and the antitumor drugs gemcitabine on living nonsmall lung cancer cells Calu-1 [71] and cisplatin on nasopharyngeal carcinoma cells [72] by Raman microscopic imaging. [67] TheR aman study detected large panitumumab-induced differences in cells expressing wild-type K-Ras,b ut not in cells with oncogenic K-Ras mutations.O ther works monitored the effects of the anticancer drug docetaxel on the morphology and biochemistry of living colon cancer cells, [68] the anticancer drug paclitaxel on MCF-7 breast cancer cells, [69] the chemotherapeutic drug doxorubicin on lymphocytes, [70] and the antitumor drugs gemcitabine on living nonsmall lung cancer cells Calu-1 [71] and cisplatin on nasopharyngeal carcinoma cells [72] by Raman microscopic imaging.…”
Section: Raman Imaging Of Single Cellsmentioning
confidence: 99%
“…[67] TheR aman study detected large panitumumab-induced differences in cells expressing wild-type K-Ras,b ut not in cells with oncogenic K-Ras mutations.O ther works monitored the effects of the anticancer drug docetaxel on the morphology and biochemistry of living colon cancer cells, [68] the anticancer drug paclitaxel on MCF-7 breast cancer cells, [69] the chemotherapeutic drug doxorubicin on lymphocytes, [70] and the antitumor drugs gemcitabine on living nonsmall lung cancer cells Calu-1 [71] and cisplatin on nasopharyngeal carcinoma cells [72] by Raman microscopic imaging. [67] TheR aman study detected large panitumumab-induced differences in cells expressing wild-type K-Ras,b ut not in cells with oncogenic K-Ras mutations.O ther works monitored the effects of the anticancer drug docetaxel on the morphology and biochemistry of living colon cancer cells, [68] the anticancer drug paclitaxel on MCF-7 breast cancer cells, [69] the chemotherapeutic drug doxorubicin on lymphocytes, [70] and the antitumor drugs gemcitabine on living nonsmall lung cancer cells Calu-1 [71] and cisplatin on nasopharyngeal carcinoma cells [72] by Raman microscopic imaging.…”
Section: Raman Imaging Of Single Cellsmentioning
confidence: 99%
“…Adapted from Pully et al 130 Reproduced with permission ß2011, from John Wiley & Sons, Inc. study was later expanded and hyper-spectral Raman images (785 nm) of lymphocytes were obtained after exposure to doxorubicin with an extra time-point at 96 h. These results showed significant differences between the biochemical trends in local and global changes of the cells, which suggested that valuable information about the entire cell can be missed if only Raman spectra of localized cell regions are used. 139 …”
mentioning
confidence: 99%
“…Usually, the statistical approaches such as partial least square regression (PLSR), Support Vector Machine (SVM) [25], and Gaussian Mixture Discriminant Analysis [26] are combined with principal components analysis (PCA) [27] to quantitatively analyze mixture by Raman or SERS. In the SAM fermentation solution, there is a mass of materials, including the water, inorganic salt, alcohol, ketone with no obvious Raman signals, and SAM with sharp characteristic peaks.…”
Section: Resultsmentioning
confidence: 99%